Aging Process of Lateral Facial Fat Compartments: A Retrospective Study. (27th February 2021) - Yang, Ching-Sheng; Huang, Yau-Li; Chen, Chun-Bing; Deng, Chih-Ying; Liu, Yu-Ting; Huang, Po-Han Patrick; Chang, Kuang-Cheng
Abstract: Background: Since 2007, when the anatomy of facial fat compartment was described, an increasing number of studies on the aging process of the compartment of cadavers has emerged. Objectives: The authors evaluated the aging changes of lateral facial fat compartments on the same person. Methods: Sixty-three patients were included in this retrospective study. All patients had magnetic resonance imaging scans with at least 4 years apart. The authors targeted the fat compartments of the superficial temporal, subcutaneous temporal, and buccal fat pad, comparing the data on different time points. Results: The thickness of the subcutaneous temporal fat did not change significantly. The 3 diameters of the superficial temporal fat compartment all became thinner on the axial view ( P < 0.05). On the sagittal view, the superficial temporal fat elongated from 38.89 mm to 43.74 mm ( P < 0.05). The buccal fat compartment also lengthened from 68.73 mm to 74.39 mm ( P < 0.05) and had a positive correlation with follow-up duration only. Conclusions: The study revealed the fat compartment change on the same person with time. The temporal hollow mainly originates from the thinner part of the superficial temporal fat. The descending of the buccal fat pad aggravates the labiomandibular fold. By understanding the aging process more fully, we can rejuvenate our patients more naturally.